MANFAAT MOTIVASI BELAJAR BERBASIS KEARIFAN LOKAL G12 - Zaitun, Zaitun (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2019)
Abstract: Learning is an obligation as well as a spiritual need of human. Especially in the global era that all sophisticated has given various consequences and influence both positive and negative. The positive value must provide good for learners but the negative value with a series of moral decadence cases such as cheating in learning activities, plagiarism, lazy, immoral, free sex, deteriorating of polite values need to be handled by the return to a moral formation which oriented in motivation. This paper offers the motivation to learn based on the local wisdom of G12 as a motivator to learn because motivation and encouragement become something important in improving the learning effort in achieving the expected goals. The purpose of this paper was to foster and improve the motivation to learn based on local wisdom G12 as well as preserve the G12 and explore the values of motivation contained therein. The method used was descriptive qualitative with content analysis as well as Peirce's semiotics where collected primary and secondary data, then described, analyzed, and so found the result and conclusion that the benefits of learning motivation based on G12 include: fostering religious values in the students, moral formation, increase the spirit of learning, enrichment of learning for educators, educators as role models in learning and inheritance of local wisdom values.Keywords: the benefits of learning motivation,  local wisdom, G12 Abstrak: Belajar merupakan kewajiban sekaligus kebutuhan rohani manusia. Apalagi di era global yang serba canggih telah memberikan berbagai konsekuensi serta pengaruh baik itu positif maupun  negative. Nilai positif pastinya memberikan kebaikan bagi peserta didik namun nilai negative dengan serentetan kasus dekadensi moral seperti mencontek dalam aktivitas pembelajaran, plagiat,malas,asusila, free sex,pudarnya nilai sopan santun perlu ditangani dengan kembali pada pembinaan akhlak berorientasi pada motivasi. Tulisan ini menawarkan motivasi belajar berbasis kearifan local G12 sebagai pendorong dan penggerak untuk belajar karena motivasi dan dorongan menjadi sesuatu yang penting dalam meningkatkan usaha belajar dalam mencapai tujuan yang diharapkan. Tujuan tulisan ini adalah untuk menumbuhkan serta meningkatkan motivasi belajar  berbasis kearifan local G12 sekaligus melestarikan G12 serta menggali nilai-nilai bermuatan motivasi yang ada didalamnya. Metode yang digunakan adalah deskriptif kualitatatif dengan dengan anaisis isi dan semiotic Pierce dimana dikumpulkan data primer dan skunder,selanjutnya di deskripsikan, dianalisis dan sehingga ditemukan hasil dan kesimpulan  bahwa manfaat motivasi belajar berbasis G12 antara lain : menumbuhkan nilai religious dalam diri peserta didik,  pembinaan akhlak mulia, meningkatkan semangat belajar, pengayaan pembelajaran bagi pendidik, pendidik sebagai role model dalam pembelajaran dan pewarisan nilai-nilai kearifan local..Kata kunci: Manfaat motivasi belajar, kearifan lokal, G12